HOTAIR interacts with PRC2 complex regulating the regional preadipocyte transcriptome and human fat distribution - Feng-Chih Kuo; Matt J. Neville; Rugivan Sabaratnam; Agata Wesolowska-Andersen; Daniel Phillips; Laura B.L. Wittemans; Andrea D. van Dam; Nellie Y. Loh; Marijana Todorčević; Nathan Denton; Katherine A. Kentistou; Peter K. Joshi; et al. (Cell Reports, 2022)
Summary: Mechanisms governing regional human adipose tissue (AT) development remain undefined. Here, we show that the long non-coding RNA HOTAIR (HOX transcript antisense RNA) is exclusively expressed in gluteofemoral AT, where it is essential for adipocyte development. We find that HOTAIR interacts with polycomb repressive complex 2 (PRC2) and we identify core HOTAIR-PRC2 target genes involved in adipocyte lineage determination. Repression of target genes coincides with PRC2 promoter occupancy and H3K27 trimethylation. HOTAIR is also involved in modifying the gluteal adipocyte transcriptome through alternative splicing. Gluteal-specific expression of HOTAIR is maintained by defined regions of open chromatin across the HOTAIR promoter. HOTAIR expression levels can be modified by hormonal (estrogen, glucocorticoids) and genetic variation (rs1443512 is a HOTAIR eQTL associated with reduced gynoid fat mass). These data identify HOTAIR as a dynamic regulator of the gluteal adipocyte transcriptome and epigenome with functional importance for human regional AT development.